A range of kindness activities boost happiness. Issue 3 (4th May 2019) - Rowland, Lee; Curry, Oliver Scott
ABSTRACT: This experiment investigates the effects of a seven-day kindness activities intervention on changes in subjective happiness. The study was designed to test whether performing different types of kindness activities had differential effects on happiness. Our recent systematic review and meta-analysis of the psychological effects of kindness (Curry, et al. 2018) revealed that performing acts of kindness boosts happiness and well-being. However, we noted in that review that rarely had researchers specifically compared the effects of kindness to different recipients, such as to friends or to strangers. Thus in a single factorial design (n=683) we compare acts of kindness to strong social ties, weak social ties, novel acts of self kindness, and observing acts of kindness, against a no acts control group. The results indicate that performing kindness activities for seven days increases happiness. In addition, we report a positive correlation between the number of kind acts and increases in happiness. Neither effect differed across the experimental the groups, suggesting that kindness to strong ties, to weak ties, and to self, as well as observing acts of kindness, have equally positive effects on happiness.